The Chinese aesthetic tradition - Li, Zehou (University of Hawaiʻi Press, 2010)
Touching on all aspects of artistic activity, Li demonstrates the fundamental role of aesthetics in the development of the cultural & psychological structures in Chinese culture that define 'humanity'.